Assessing the effectiveness of planned teaching programme on knowledge regarding human rights of mentally ill among B.Sc. nursing students - Shukla, Garima; Singh, Vir Vikram Sahdev (International Journal Of Community Medicine And Public Health, 2025)
Background: As per the amendments in mental health care act 2017 regarding the rights of mentally ill is highly affected on basis of knowledge among the nursing professional students that helps to maintain the quality care of the future nurses. Objectives were to assess the level of knowledge regarding human rights of mentally ill among B. Sc. nursing students, to evaluate the effectiveness of planned teaching program on knowledge regarding human rights of mentally ill, and to find out the association between level of knowledge regarding rights of mentally ill among B. Sc. nursing student in selected nursing college at Meerut. Methods: Pre-experimental, convenient sampling study was done among 90 samples of B. Sc. nursing students with structured questionnaire. Results: The effectiveness of the planned teaching program on knowledge regarding human rights of mentally ill individuals among B. Sc. nursing students. The mean pretest knowledge score was 12.53±3.535, while the post-test mean score increased to 19.31±3.871. Conclusions: Study reveal that the majority of students (82.2%) have an adequate level of knowledge after the intervention, while 17.8% have an inadequate level of knowledge indicate planned teaching program was effective and participant knowledge was improved.